1992
DOI: 10.1139/v92-283
|View full text |Cite
|
Sign up to set email alerts
|

Short syntheses of rigid acyclic or macrocyclic poly-imine ligands and their use in Ru(II), Fe(III), and alkali metal complexation

Abstract: ROBERT DASH and PIERRE G. POTVIN. Can. J. Chem. 70, 2249 (1992. Lipophilic derivatives of 2,6-bis(3-pyrazoly1)pyridine and 1,3-bis (3-pyrazoly1)benzene were obtained in acceptable yields by Stork reactions and transformed by N-alkylations into three pentadentates, three bis(bidentates), and one macrocyclic octadentate ligand. The parent bis(pyrazoly1) pyridine constituted a terpyridine analogue and readily formed a Ru(I1) complex. By comparison of 'H nuclear magnetic resonance patterns, it was found that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
(21 reference statements)
1
6
0
Order By: Relevance
“…This facility has enabled us to prepare a variety of substituted tridentates 8,11,12 and a ditopic bis(tridentate) 11 as well as novel pentadentate and macrocyclic 7 ligands. We have also demonstrated how these ligands can bind alkali metal ions, Fe(III), Ru(II), ,, Zn(II), and Co(II). , The liposolubilities of H 1 and H 2 2 and their derivatives and complexes have proven to be synthetically very advantageous.
…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This facility has enabled us to prepare a variety of substituted tridentates 8,11,12 and a ditopic bis(tridentate) 11 as well as novel pentadentate and macrocyclic 7 ligands. We have also demonstrated how these ligands can bind alkali metal ions, Fe(III), Ru(II), ,, Zn(II), and Co(II). , The liposolubilities of H 1 and H 2 2 and their derivatives and complexes have proven to be synthetically very advantageous.
…”
Section: Introductionmentioning
confidence: 92%
“…We wished to similarly examine complexes of the tridentate analogue of H 1 , the symmetrical 2,6-di(tetrahydroindazol-3-yl)pyridine H 2 2 , which is also easily prepared. , Like H 1 but unlike the 1‘( N ‘),2-linkage isomers, , H 2 2 is amenable to modification at the 1( N )-H sites. This facility has enabled us to prepare a variety of substituted tridentates 8,11,12 and a ditopic bis(tridentate) 11 as well as novel pentadentate and macrocyclic 7 ligands.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that treatment of bis(pyrazolyl)pyridine 3 with NaH in THF, followed by alkylating agents, leads exclusively to out,out - or 1‘,1‘‘-disubstituted bis(indazol-3-yl)pyridines. , Thus, exhaustive methylation of 3 (2.4 equiv of NaH/THF/room temperature/2.3 equiv of CH 3 I) produced regiomerically pure 1a in 60% isolated yield . Metal chelation was apparently critical in directing the regiochemistry and organic bases, such as DBU or Et 3 N, generated complicated mixtures of out,out , in,out , and in,in regiomers.…”
Section: Resultsmentioning
confidence: 97%
“…A suitable class of tridentate building blocks are the 2,6-bis(tetrahydroindazol-3-yl)pyridines 1 . They and their bidentate cousins comprise a class of newly developed ligands for transition metals which are readily prepared from commercially available materials by short routes and in good yields. They are lipophilic and readily form stable, organo-soluble Ru(II), ,, Zn(II), and Co(II) complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation